Respuesta :
Using the distributive property, 10x + 20.
(5 * 4) + (5 * 2x) = 20 + 10x = 10x + 20.
(5 * 4) + (5 * 2x) = 20 + 10x = 10x + 20.
Hello!
The problem given in the image above has asked us to simplify the expression using the Distributive Property. The Distributive Property states the following:
a(b + c) = ab + ac
a(b – c) = ab – ac
In this case, we’ll use the first of the two formulas. Insert any known values given in the original equation:
a(b + c) = ab + ac
5(4 + 2x) = 5(4) + 5(2x)
Now simplify the right side of the equation:
5(4) + 5(2x) = 20 + 10x
We have now proven that 5(4 + 2x) is equivalent to the expression 20 + 10x.
I hope this helps!
The problem given in the image above has asked us to simplify the expression using the Distributive Property. The Distributive Property states the following:
a(b + c) = ab + ac
a(b – c) = ab – ac
In this case, we’ll use the first of the two formulas. Insert any known values given in the original equation:
a(b + c) = ab + ac
5(4 + 2x) = 5(4) + 5(2x)
Now simplify the right side of the equation:
5(4) + 5(2x) = 20 + 10x
We have now proven that 5(4 + 2x) is equivalent to the expression 20 + 10x.
I hope this helps!